The Influence of Cosplaying in Increasing Japanese Language and Culture Learning at Binus University - Wishnoebroto Wishnoebroto; Roberto Masami Prabowo; Alex Jhon (Humaniora, 2017)
This research was intended to see the prospect of whether the significance of cosplay subculture had given certain influence towards these colorful communities. The target population was Bina Nusantara University students who were either in Japanese Department or those who were interested in Japanese culture. By utilizing the online questionnaire, this research used qualitative random sampling approach and expected to be used as a reference in designing the future curriculum since it was quite applicable and relevant to the condition in Indonesia. Based on the findings, cosplaying has been proven to be a beneficial activity that may help and motivate the learners to understand Japanese language and culture. Finally, the researchers suggest building Japanese language curricula based on the cosplaying activity that may be implemented soon to attract Japanese enthusiasts.